Epidemiology and pathology of onchocercosis of cattle in Bangladesh (Progressive Agriculture, 2015)
Onchocercosis is a parasitic disease caused by the different species of nematodes belonging to the genus Ochocerca affecting both humans and animals.  Ochocerca armillta, O. gutturosa and O. gibsoni affect mainly cattle, and also buffaloes. Here, we studied epidemio-pathology and vector flies of onchocercosis in cattle in Bangladesh. Out of 310 animals examined, 163 (52.6%) were infected with different species of Onchocerca.  Three species of Onchocerca, namely, Onchocerca armillata (24.8%), Onchocerca gutturosa (24.7%) and Onchocerca gibsoni (13.3%) were identified.  We recovered O. armillata only from aorta, O. gutturosa from the ligamentum nuchae and O. gibsoni from the subcutaneous nodules. Nodular lesions were detected at the neck (49/20.9%), abdomen (5/2.1%), flank (8/3.4%), brisket (33/14.0%) and thigh/legs (32/13.6%) regions. We observed age as a potential diterminant in the occurance of the infection.  Prevalence of O. armillata and O. gutturosa was significantly higher in older animals (> 4 years) than yearlings (1-2 years).  Sex, breed and rearing system did not significantly influence the prevalence of bovine onchocercosis.  Our study revealed that seasons of the year was another important determinant for onchocercosis, and prevalence was the highest in the summer. Grossly, the affected aorta was thickened, dilated and with elevated intima. Histological examination revealed parasitic granuloma present in blood vessels characterized by the infiltration of eosinophils and neumerous sections of the parasites. We identified only Culicoides spp., but no Simulium spp., as a vector from the study area. Vector flies were the most abundant in the early morning and least at noon, and mostly at the umbilical region of cattle. Culicoides spp. were most abundant in the winter. Our results suggest that occurrence of onchocercosis is fairly high in cattle in Bangladesh irrespective to age, sex, breed and management.Progressive Agriculture 26 (2): 147-154, 2015